2024
DOI: 10.3847/1538-4357/ad138a
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Constraints on the Hot Gaseous Corona of Edge-on Late-type Galaxies in Virgo

Meicun Hou,
Lin He,
Zhensong Hu
et al.

Abstract: We present a systematic study of the putative hot gas corona around late-type galaxies (LTGs) residing in the Virgo cluster, based on archival Chandra observations. Our sample consists of 21 nearly edge-on galaxies representing a range of star formation rate (SFR) of 0.2–3 M ⊙ yr−1 and a range of stellar mass (M *) of (0.2–10) × 1010 M ⊙, the majority of which have not been explored with high-sensitivity X-ray observations so far. Signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 92 publications
0
5
0
Order By: Relevance
“…reported that a total of 39 nuclear X-ray sources are present among the 75 LTGs in Virgo with a typical detection limit of ∼3 × 10 38 erg s −1 and a completeness limit of ∼10 39 erg s −1 in the 0.3-10 keV band, but without quoting the exact host galaxies. As a byproduct of our recent study of diffuse hot gas in these LTGs (Hou et al 2024), we have independently detected 35 nuclear X-ray sources. Among them, 13 share the same host galaxy as the eRASS1 nuclear sources.…”
Section: Identification Of Nuclear X-ray Sourcesmentioning
confidence: 99%
“…reported that a total of 39 nuclear X-ray sources are present among the 75 LTGs in Virgo with a typical detection limit of ∼3 × 10 38 erg s −1 and a completeness limit of ∼10 39 erg s −1 in the 0.3-10 keV band, but without quoting the exact host galaxies. As a byproduct of our recent study of diffuse hot gas in these LTGs (Hou et al 2024), we have independently detected 35 nuclear X-ray sources. Among them, 13 share the same host galaxy as the eRASS1 nuclear sources.…”
Section: Identification Of Nuclear X-ray Sourcesmentioning
confidence: 99%
“…This sample spans a substantial range in galaxy morphology, including early-type spirals (i.e., with a substantial bulge), disk-dominated spirals, and irregular galaxies. A recent work of Hou et al (2024a) selected among these 75 LTGs a subsample of 21 nearly edge-on disk galaxies to study the putative diffuse hot-gas corona under the influence of the ICM. Since the focus of the present work is to probe an extraplanar population of discrete X-ray sources, we adopt nearly the same edge-on LTGs as in Hou et al (2024a), with the exception of two galaxies, NGC 4302 and NGC 4343.…”
Section: Sample Selectionmentioning
confidence: 99%
“…A recent work of Hou et al (2024a) selected among these 75 LTGs a subsample of 21 nearly edge-on disk galaxies to study the putative diffuse hot-gas corona under the influence of the ICM. Since the focus of the present work is to probe an extraplanar population of discrete X-ray sources, we adopt nearly the same edge-on LTGs as in Hou et al (2024a), with the exception of two galaxies, NGC 4302 and NGC 4343. NGC 4302 is too close to its neighbor galaxy NGC 4298, which makes it difficult to separate the X-ray sources belonging to the individual galaxies.…”
Section: Sample Selectionmentioning
confidence: 99%
See 2 more Smart Citations